The influence of employees' perception of over-qualification on career compromise: Mediated by role conflict and sense of relative deprivation - Zhou, Xiaogang; Zhang, Yunxi; Lin, Yanyan; Li, Liqing (Frontiers in Psychology, 2023)
In the external environment with the increasing level of education, there is a general phenomenon of excess qualification in the employment market. This research discusses employee career compromise from the perspective of employee over-qualification based on resource conservation theory and self-regulation theory. Combined with the survey data, a structural equation model (SEM) is constructed, and the mediation effect of relative deprivation and role conflict is analyzed according to the causal mediation model. The research find that employees' perception of over-qualification has three ways to affect employees' career compromise. First, employees' perception of over-qualification has a significant positive impact on their career compromise behavior through employees' emotions and self-cognition. Second, role conflict plays a partial intermediary role between the perception of over-qualification and career compromise by positively affecting career compromise behavior. Third, the sense of relative deprivation plays a partial intermediary role between the perception of over-qualification and career compromise by negatively affecting career compromise behavior. According to the research conclusions, the following suggestions are put forward. Enterprises need to establish a scientific employment mechanism to achieve talent-post matching and fundamentally reduce the phenomenon of over-qualifications. The company should pay attention to employee training, actively guide employees' career planning, instruct employees to correctly understand the sense of over-qualification and play a positive role in guiding employees' career planning.